Educating Community Health Professionals About the Health-Related Effects of Climate Change Through ECHO Telementoring. (May 2022) - Katzman, Joanna G.; Tomedi, Laura E.; Herring, David; Jones, Hunter; Groves, Ralph; Norsworthy, Kent; Martin, Chamron; Liu, Jinyang; Kazhe-Dominguez, Briana; Arora, Sanjeev
Introduction: Climate change is a global public health emergency causing extensive morbidity and mortality worldwide. Although most large medical organizations endorse the need to train health care professionals in climate change, such trainings are not readily available. Methods: This article describes the results of an 8-week, 75-min per week, Climate Change and Human Health ECHO (CCHH ECHO) synchronous telementoring course for post-licensure health professionals. The primary goals were: to increase knowledge, self-efficacy, and communication skills. Participants were eligible to receive up to 10 h of no-cost continuing education credits and a certificate for completing the program. Results: The 8-week course included 625 unique participants from 25 countries. An interprofessional group of clinicians, health professionals, and educators included: 130/28% PhD, 92/20% MD/DO, 52/12% RN/NP/PA, 50/11% MPH. The prospective survey demonstrated a significant improvement in knowledge, confidence, attitudes ( P < .001) and communication skills ( P = .029) at 3 months post course. Conclusions: The climate crisis is a public health emergency, and health professionals worldwide are considered the most trusted source of health information. Training current and future health professionals regarding the health-related effects of global warming is vital. The CCHH ECHO may be a successful model to facilitate knowledge transfer and promote communication skills between subject matter experts and course participants.